The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12291-011-0185-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antiresorptive Therapy on Urinary Hydroxyproline in Postmenopausal Osteoporosis

Abstract: Osteoporosis becomes a serious health threat for older postmenopausal women by predisposing them to an increased risk of fracture. Osteoporosis and associated fractures are an important cause of morbidity and mortality. Special attention is being paid to early detection, management, and treatment of postmenopausal osteoporosis in women. Biochemical markers can enable dynamic and rapid measurement of total body skeletal metabolism and will be clinically useful in the management of postmenopausal osteoporosis wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Approximately 10% of released HyP circulates in blood in the protein-bound form. These proteins are filtered and excreted into the urine without metabolic alterations [32,33]. It is considered that collagen is one source of HyP in the body.…”
Section: Hydroxyproline (Hyp)mentioning
confidence: 99%
“…Approximately 10% of released HyP circulates in blood in the protein-bound form. These proteins are filtered and excreted into the urine without metabolic alterations [32,33]. It is considered that collagen is one source of HyP in the body.…”
Section: Hydroxyproline (Hyp)mentioning
confidence: 99%
“…HYP is an unique amino acid for maintaining cell structure and function, and is a major component of collagen ( 62 ). Excessive acids, MMPs and cathepsin K, could degrade collagen I into HYP ( 63 ). Prakobwong et al ( 35 ) found that the plasma levels of HYP and collagen I were significantly higher in opisthorchiasis patients compared with healthy individuals.…”
Section: Serum Makersmentioning
confidence: 99%
“…Most of postmenopausal women are high risk for developing this disease. After menopause there was a massive reduction of bone mass that leads to an imbalance of bone resorption and formation [53]. There are numerous factors for the etiology of postmenopausal osteoporosis such as aging, genetic, environmental, hormonal, nutritional, and life style factors [54].…”
Section: Bone Mineralizationmentioning
confidence: 99%